Brilliant inks : a step-by-step guide to creating in vivid color : draw, letter, paint, print, and more! - Sokolova, Anna, 1985- (Quarry Books, 2022)
"Brilliant Inks offers beginners and beyond exciting techniques, lessons, and projects for painting, drawing, and lettering with vibrant colored inks. Apply these skills to eye-catching projects that include jewelry, accessories, dimensional artwork, and more"--